EFEKTIVITAS KEGIATAN PUSAKA SAKINAH SEBAGAI UPAYA PEMBINAAN KETAHANAN KELUARGA DALAM MENEKAN PERCERAIAN - Muhammad Fauzi Alamsyah; Musyaffa Amin Ash Shabah; Oni Wastoni (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2023)
This study aims to determine the effectiveness of Pusaka Sakinah activities to foster family resilience in suppressing divorce by the KUA of Tambun Selatan District. This study uses a qualitative research method, with the type of research used being socio-legal research, a legal science research approach that uses the help of social sciences. Data analysis techniques were carried out through several predetermined stages, namely identification and classification, and then interpreted by explaining descriptively. The study results explained that the concept of Sakinah heritage activities, the hallmark of the program implemented by the KUA of Tambun Selatan District, is fairly effective. The material presented in these activities is the formation of each individual male or female character in establishing household relationships. So that every husband and wife pair have the provision of understanding and experience in building a household, the problems that occur can be resolved properly. The Sakinah Family Service Center, or in the future referred to by the acronym "Pusaka Sakinah," is an activity for the community that functions to facilitate and provide continuous consultation and guidance to create a sakinah family.